Redescription of types of Sphecodes (Austrosphecodes) (Hymenoptera: Halictinae) from Argentina and Brazil - Gonçalves, Rodrigo B (Zootaxa, 2017)
Here I provide taxonomic notes on types of Sphecodes (Austrosphecodes) which are deposited in South American institutions. Sphecodes andinus Schrottky, 1906, S. brasiliensis Schrottky, 1910, S. bruchi Schrottky, 1906, S. cordillerensis Jörgensen, 1912, S. coriae Moure & Hurd, 1987, S. inornatus (Schrottky, 1902), S. melanopus Schrottky, 1906, S. mendocinus Jörgensen, 1912, and S. minarum Schrottky, 1910 are redescribed. The male of S. brasiliensis, S. convergens Michener, 1978, and the female of S. inornatus are described for the first time. The lectotype of Halictus meridionalis Jörgensen, 1912 is presently designated.